A 1H NMR-based metabonomic investigation of time-dependent metabolic trajectories in a high salt-induced hypertension rat model. Issue 1 (28th November 2014) - Wang, Linlin; Zheng, Lingyun; Luo, Ren; Zhao, Xiaoshan; Han, Zhihui; Wang, Yaling; Yang, Yongxia
Abstract : The time-dependent metabolic profiles in urine, plasma and feces of salt-fed hypertensive rats were systematically investigated using NMR-based metabonomics. Abstract : High salt-induced hypertension (HT) is an increasingly relevant health issue. However, the molecular mechanism of the metabolic transformation in HT development remains largely unknown. Features of the time-dependent metabolic transfer during HT onset and development should describe crucial aspects of HT phenotypes and may allow early prevention. To investigate the progression of HT and identify potential biomarkers, the metabolic profiles of urine, plasma, and fecal extracts of HT rats fed a high salt diet were investigated using a 1 H nuclear magnetic resonance (NMR)-based metabonomics approach. In this study, the profiles at the 4th and 8th weeks for urine and fecal extracts could be classified, which revealed progression axes from normal status to HT status. Changes in succinate, α-ketoglutaric acid (α-KG), citrate, creatine and creatinine, choline, phosphocholine (PC) and glycerophosphocholine (GPC), trimethylamine- N -oxide and betaine, taurine and hippurate in urine, in conjunction with gut flora disturbance in feces were observed during the initial stage of HT (6th week). During the severe HT period (8th week), these metabolic changes became more pronounced, and the metabolic disturbance in plasma lipid and choline indicated a possible increased risk of cardiovascular diseases. Thus, an increase in dietary salt can induce a series of metabolic changes, and 1 H NMR-based metabonomics offers a non-invasive means to elucidate the progression of HT induced by this dietary pattern.